2000
DOI: 10.2118/62051-pa
|View full text |Cite
|
Sign up to set email alerts
|

Barite Sag: Measurement, Modeling, and Management

Abstract: A joint industry project was established to study barite sag mechanisms and to develop field guidelines to manage the consequences. A simple empirical model was developed to compare sag potential for a wide range of fluid types. In the study, physical properties of the mud, wellbore conditions, and characteristics of the weighting material were shown to have a large influence on sag behavior. The study also included direct measurements of the properties of settled weight-material beds. These results provide ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…In order to check the stability against settling of weight material, the oil-based MBS fluid was tested in a large scale flow loop following the test design described by Bern, et al 1 The oil-based MBS fluid was compared to a conventional HTHP oil-based fluid. In this test the influence of flow velocity and pipe rotation on dynamic barite sag is monitored.…”
Section: Fluid Formulation and Initial Properties The Fluid Formulatmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to check the stability against settling of weight material, the oil-based MBS fluid was tested in a large scale flow loop following the test design described by Bern, et al 1 The oil-based MBS fluid was compared to a conventional HTHP oil-based fluid. In this test the influence of flow velocity and pipe rotation on dynamic barite sag is monitored.…”
Section: Fluid Formulation and Initial Properties The Fluid Formulatmentioning
confidence: 99%
“…It has been well documented in the literature that the potential for sag is considerably higher in oil-based drilling fluids when compared to their water-based counterparts. 1,2,3,4,5,6 The heightened tendency for sag in nonaqueous fluids is believed to be a function of the differences in structural build-up or the gelling mechanisms of the two systems. Consequently, employing conventional weight materials in the development of oil-based drilling fluids for HTHP drilling that possess acceptable rheology to minimize ECD while also maintaining satisfactory sag stability has been very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that dynamic sag is partially related to low shear rate viscosity. The results of experimental studies by Bern et al (1996Bern et al ( , 1998) employed a dynamic sag flow loop. The apparatus contained an annulus with controllable eccentricity and the ability to induce relative rotation between the inner and outer walls.…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…Barite sag in IEF is countered with a viscoelastic gel behavior (Sasson et al 1995;Sasson et al 1991) or increased low-shear rheology (Dye et al 1999;Kenny 1996). The low shear rheology is characterized by the low shear yield point (LSYP), typically a value from 7-15 lb/100ft 2 (Bern et al 1996;Bern et al 2000), is believed to impart sag resistance to the IEF. In the organoclay free IEF, low-gravity solids (clay-type materials and micronized calcium carbonate) are added to improve the rheology of the IEF.…”
Section: Introductionmentioning
confidence: 99%
“…This ability of the nanoparticles to provide stable water in oil emulsion has been used to formulate stable organoclay-free invert emulsion fluids free of low gravity solids like calcium carbonate and other clay-type materials. The nanoparticles used in the organoclay-free IEF provide good sag resistance without drastically increasing the fluid rheology, which usually delivers a viscous IEF with increased ECD (Bern et al 1996;Bern et al 2000).…”
Section: Introductionmentioning
confidence: 99%